The roles of work motivation and job involvement on the relationship between contextual factors and creative behavior - Daratul Ambia, Che Mit (2017)
The main purpose of this study was to investigate the factors that influence creative behavior among Malaysian researchers. Specifically, it investigated the mediating effect of work motivation on the relationships between the contextual factors, namely stressors, autonomy, culture, reward and supervisory style on creative behavior; the effect of work motivation on creative behavior; and the moderating effect of job involvement on the relationships between stressors, autonomy, culture, reward and supervisory style, and work motivation. Creativity is considered as the seed of innovation, where innovativeness has been considered as one of the fundamentals for organizational competitiveness. Acknowledging the importance of creative behavior on innovation, this study was carried out to investigate its predictors, and to include work motivation as the mediating factor and job involvement as the moderating variable between the contextual factors and work motivation. Accordingly, this study was based on the self-determination theory (SDT) and the organizational support theory (OST) to position the possible relationships between the variables in the research framework. A total of 201 researchers, representing a response rate of 40.8%, participated in this study. Data were collected via questionnaires. PLS-SEM was used to analyze the data and test the hypotheses. This study found that the level of creative behavior among the researchers was high. Statistical results showed that the relationship between stressors, work motivation, creative behavior as well as the relationship between autonomy, work motivation and creative behavior were supported. Work motivation was also found to be positively related to creative behavior. Empirical support was also found for the moderating effect of job involvement on the relationships between stressors and supervisory styles and work motivation. The theoretical and practical implications alongside recommendations for future research are discussed.